Penggunaan Pasir Seragam pada Perbaikan Subgrade Ditinjau Terhadap Tebal Perkerasan Jalan (Swelling Potential dan Non Swelling Potential) - Pratiwi, Ayu Ning Trias; Iswan, Iswan; Zakaria, Ahmad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
Subgradeis the most important part to be used as the focus and support of all construction loads that are on it. If the subgrade is clay soil that has a low carrying capacity and is very sensitive to moisture content, then nearby buildings will often suffer damage, such as land located in Marga Kaya Village. In this study using the method of mixing native soil with stabilization material in the form of uniform sand derived from Mount Sugih with a mixture variation of 5%, 10% and 15% of the dry weight of the soil. The test results showed cbr unsoaked and soaked maximum occurred in sand mixture 15% with CBR Unsoaked value of 13.2% and CBR Soaked with a value of 2.9%. Road pavement thickness on CBR Unsoaked and Soaked efficiently on sand mixture 15% with thickness D1 = 2.75 cm, D2 = 20 and D3 = 10 cm, and CBR Soaked with thickness D1 = 8.75 cm, D2 = 20 cm and D3 = 10 cm. The value of swelling decreased from 11.4% to 7.4% in the addition of uniform sand by 15%. DDT value is influenced by cbr value the greater cbr value then DDT will increase.